Spatial horizontal inequality and the Maoist insurgency in Nepal - S. Mansoob Murshed; Scott Gates (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
The Maoist insurgency in Nepal is one of the highest intensity internal conflicts in recent times. Investigation into the causes of the conflict would suggest that grievance rather than greed is the main motivating force. The concept of horizontal or inter-group inequality, with both an ethnic and caste dimension, is highly relevant in explaining the Nepalese civil war. There is also a spatial aspect to the conflict, which is most intense in the most disadvantaged areas in terms of human development indicators and land holdings. Using the intensity of conflict (fatalities) as the dependent variable and HDI indicators and landlessness as explanatory variables, we find that the intensity of conflict across the districts of Nepal is significantly explained by the degree of inequalities. – Nepal ; Maoist insurgency ; spatial inequality ; horizontal inequality
Keywords: D30; D74; R11; 330; Regionale Disparität; Politische Unruhen; Nepal